Dcf1 Deficiency Attenuates the Role of Activated Microglia During Neuroinflammation - Wang, Jiao; Li, Jie; Wang, Qian; Kong, Yanyan; Zhou, Fangfang; Li, Qian; Li, Weihao; Sun, Yangyang; Wang, Yanli; Guan, Yihui; Wu, Minghong; Wen, Tieqiao (Frontiers in Molecular Neuroscience, 2018)
Microglia serve as the principal immune cells and play crucial roles in the central nervous system, responding to neuroinflammation via migration and the execution of phagocytosis. Dendritic cell-derived factor 1 (Dcf1) is known to play an important role in neural stem cell differentiation, glioma apoptosis, dendritic spine formation, and Alzheimer’s disease, nevertheless, the involvement of the Dcf1 gene in the brain immune response has not yet been reported. In the present paper, the RNA-sequencing and function enrichment analysis suggested that the majority of the down-regulated genes in Dcf1-/-（Dcf1-KO）mice are immune-related. In vivo experiments showed that Dcf1 deletion produced profound effects on microglial function, increased the expression of microglial activation markers, such as ionized calcium binding adaptor molecule 1 (Iba1), Cluster of Differentiation 68 (CD68) and translocator protein (TSPO), as well as certain proinflammatory cytokines (Cxcl1, Ccl7, and IL17D), but decreased the migratory and phagocytic abilities of microglial cells, and reduced the expression levels of some other proinflammatory cytokines (Cox-2, IL-1β, IL-6, TNF-α, and Csf1) in the mouse hippocampus. Furthermore, in vitro experiments revealed that in the absence of lipopolysaccharide (LPS), the majority of microglia were ramified and existed in a resting state, with only approximately 10% of cells exhibiting an amoeboid-like morphology, indicative of an activated state. LPS treatment dramatically increased the ratio of activated to resting cells, and Dcf1 downregulation further increased this ratio. These data indicated that Dcf1 deletion mediates neuroinflammation and induces dysfunction of activated microglia, preventing migration and the execution of phagocytosis. These findings support further investigation into the biological mechanisms underlying microglia-related neuroinflammatory diseases, and the role of Dcf1 in the immune response.